Prevention of radioactive pollution: A comparative simulation study on the reduction of several important radionuclides by pyrite and magnetite - Yu, Haoqi; Yu, Tao; Zeng, Kai (Frontiers in Environmental Science, 2022)
In order to ensure the long-term effective isolation of radionuclides from human beings to the environment, pyrite and magnetite, which exist widely and stably in the geological environment, can be considered to reduce the strong mobility of high-valence redox-sensitive nuclides to the low-valence nuclides with low mobility. In this work, the reducing reaction between pyrite, magnetite, and redox-sensitive radionuclides (U, Se, Tc, and Np) in the Gansu proposed-treatment plant area was under simulation by PHREEQC. Due to the considerable existence of quartz and calcite in the Gansu proposed-treatment plant area surrounding the rock of interest, the influence of the dissolved Ca2+ and SiO32- should be taken into account. The corresponding precipitation saturation index of the complex (UOX, Se(s), and TcO2) and species of interest was calculated, and the results suggested that pyrite can significantly reduce the high-valence radionuclides (U, Se, Tc, and Np), and their corresponding precipitation saturation indexes (SIs) were usually positive. However, magnetite, in a given condition, showed a certain reducing effect against Se and Np and a poor effect on U and Tc. It was worth noting that the aqueous pH in the system always remained constant because of the CO2 partial pressure of the underground biosphere under this long-term time scale. These conclusions have an important guiding significance for the prevention and retention of radioactive pollution released into the biological environment.